EFFECTIVENESS OF ROUTINE URINE ANALYSIS OF PATIENT ATTENDING RURAL HEALTH CENTERS IN ABBOTTABAD - Hanif, Ruhila; Ally, Sirajuddin Hassan; din, Jalal -ud-; Khan, Khalid (Journal of Ayub Medical College Abbottabad, 2006)
Background: Renal diseases may be discovered accidentally during routine urinalysis. This study was done to see the significance of urinalysis and study the magnitude of abnormal urinalysis in patients with no symptoms of renal disease. Methods: From 15th February to 16th March 2005, a total of 1000 samples of urine were collected from the patients attending three rural health centers of Abbottabad. Dipstick Method was used for urinalysis. Results: there were 600 males and 400 female patients. The age ranged from 1 to 55 years. Proteinuria was present in 2.3%, hematuria in 4.8 % patients, pyuria in 10.2% and glycosuria in 2% patients. Conclusion: In our setup routine urine analysis should be performed in all patients to identify the presence of unrecognized renal diseases which may benefit from simple therapeutic measures. Keywords: Urine, urinalysis, Proteinuria